Infantile Onset Encephalomyopathy, Heart Block, and Sensorineural Hearing Loss: RMND1-Associated Mitochondrial Disease - Nagappa, Madhu; Vandana, V.P.; Chiplunkar, Shwetha; Govindaraj, Periyasamy; Ponmalar, J.N. Jessiena; Gayathri, Narayanappa; Sinha, Sanjib; Taly, Arun B.; Sankaran, Bindu Parayil (Journal of Pediatric Neurology, 2020)
Mutations in RMND1 (required for mitotic division-1) has been associated with infantile onset mitochondrial disease and combined oxidation phosphorylation deficiency. This report describes a girl child of Indian origin with RMND1-associated mitochondrial disease. This 13-month-old girl, born to consanguineous parents presented with gradual loss of acquired milestones and recurrent vomiting from 5 months of age. She experienced failure to thrive, profound hypotonia, areflexia, and sensorineural deafness. Evaluation showed elevated serum lactate and complete heart block. Audiological evaluation done at 6 and 13 months of age revealed bilateral A type tympanogram, bilateral absent stapedial reflexes, absent otoacoustic emissions (OAE), and absent brainstem auditory evoked responses suggestive of bilateral profound sensorineural hearing loss. Muscle biopsy revealed evidence of ragged red fibers, ragged blue fibers, and Cytochrome coxidase (COX) deficient fibers on histochemistry and multiple complex deficiency on spectrophotometry. Exome sequencing revealed homozygous stop-loss variation, c.1349G > C, in exon 12 of RMDN1 resulting in substitution of amino acid serine for stop codon at position 450 and subsequent elongation of the protein by 31 amino acids (p.Ter450SerextTer31) which was verified by Sanger's sequencing. This report further strengthens the phenotype genotype correlations in RMND1-associated mitochondrial disease, especially the occurrence of the reported variation in South Asian patients. In addition, familiarity with the phenotype might help the physician to do targeted metabolic testing and facilitate appropriate early interventions.
Keywords: RMND1; encephalomyopathy; heart block; sensory neural hearing loss